A comparative analysis of total serum miRNA profiles identifies novel signature that is highly indicative of metastatic melanoma: a pilot study. (September 2013) - Greenberg, Eyal; Besser, Michal J.; Ben-Ami, Eytan; Shapira-Frommer, Ronnie; Itzhaki, Orit; Zikich, Dragoslav; Levy, Daphna; Kubi, Adva; Eyal, Eran; Onn, Amir; Cohen, Yehudit; Barshack, Iris; et al.
Abstract Context: Quantification of circulating microRNAs (miRNAs) has recently become feasible and reliable, with most efforts focusing on miRNAs overexpressed by cancer cells. Objective: Identification of a characteristic circulating miRNAs profile in melanoma patients. Methods: We conducted a pilot study comprised of unbiased qPCR comparison of serum miRNA profiles between metastatic melanoma patients and healthy donors. Results: Loss of two normal serum-miRNAs, miR-29c and miR-324-3p, is highly indicative of metastatic melanoma. Hierarchical clustering analysis supported the results and clearly distinguished melanoma patients from healthy donors, metastatic colon and renal cancer patients. Discussion and conclusions: This approach is independent of tumor heterogeneity and is expected to have superior biomarker performances.